Emblematic uses in viceroyalty of Peru: Some examples in Juan de Espinosa Medrano work - Sabena, Julia (2011)
This article accounts for the impact and importance of the emblematic use of reading and writing that prevailed in the Spanish viceroyalties in the Golden Ages, specially in the work of the cusqueño Juan de Espinosa Medrano. The discursive use of the emblems relates with the preponderance of images during the Baroque and provides controvers ial,religious,praiseful or condemning nuances as appropriate.With this purpose,it uses a tradition of re-readings,additions and changes that make up a universe whose exploration is necessary for the correct attribution of a correct meaning in a great quantity of golden texts.